Judicial Inconsistencies and Legislative Gaps in Service Period Agreements for Special Treatment: An Empirical Study - Ying Xiong (Studies in Law and Justice, 2025)
Along with the constant growth of the demand for advanced talents in our labor market, more and more employers are attracting talents by offering special treatment. Based on the principle of consideration in contracts, the service period system for special treatment has emerged. However, the 22nd article of the Labor Contract Law, which is also known as the “sponsored training service period” in academic circles, raises questions about whether the service period for special treatment is legally recognized. The academic community has different views on this issue. For disputes between employers and employees regarding the service period for special treatment, the views of the courts across the country are not consistent. Through the collection and sorting of judicial cases on the service period for special treatment, this article finds that the main problems in such cases are inconsistent identification of the nature of the service period, huge differences in the standard of return of special treatment, and weak legal support and logical reasoning in the reasoning part. Based on the problems existing in judicial practice, this article suggests that the legislation should expand the scope of service period, increase the review of service period reasonableness, unify the standard of return of special treatment, and restructure the existing default penalty system to match it. In this way, the service period system in labor contracts can be improved.